Engine performance and emissions from fuels containing nitrogen and sulphur. (May 2022) - Obeid, Farah; Van, Thuy Chu; Horchler, Eva Johanna; Guo, Yi; Verma, Puneet; Miljevic, Branka; Brown, Richard J.; Ristovski, Zoran; Bodisco, Timothy; Rainey, Thomas
Graphic abstract: Highlights: N and S content in fuel affected its physical properties. N and S content reduced fuel high heating value and flash point. N and S containing fuels emitted lower CO and HC. N and S containing fuels boosted NOx and SO2 . Fuel sulphur content resulted in an increase of PM2.5 . Abstract: Surrogate fuels for hydrothermal liquefaction (HTL) algae biocrude depicting its nitrogen (N) and sulphur (S) content were simulated in this study and tested in a multi-cylinder diesel engine. The influence of N and S presence in the fuel on its combustion behaviour and emissions profile was investigated. To our knowledge, N and S-containing fuels in reference to HTL algae biocrude, have not been reported in an internal combustion engine in the literature, which is the unique and novelty of the current work. The presence of N and S in the fuel affected its physical properties. The density of the surrogate fuel was slightly higher than that of diesel, while viscosity, in general, was maintained. The flash point of the N and S-fuel was reduced in the presence of N. N had a stronger effect than S in reducing the lower heating value (LHV) of the surrogate fuel than that of diesel. Compared to diesel, emissions of both carbon monoxide (CO) and unburned hydrocarbons (HC) were lower for N and S-containing fuels. Increasing nitrogen oxides (NOx ) and sulphur dioxide (SO2 ) emissions were observed with increasing N and S content, respectively, in the fuels. A significant increase in particle mass (PM) emissions was observed at high concentrations of N (4.5 wt%) and S (0.2–0.4 wt%). Such values of S are found in some off-road and marine applications. Therefore, HTL biofuel can be a low-sulphur alternative fuel for shipping industry because its fuel properties similar to that of bunker fuel.